Tumbling Into Queer Utopias and Vortexes: Experiences of LGBTQ Social Media Users on Tumblr. Issue 12 (15th October 2019) - Cavalcante, Andre
ABSTRACT: Drawing on one year of fieldwork with LGBTQ youth, I explore the ways Tumblr, a microblogging and social networking site, has become a vibrant center of queer discourse and collectivity. I argue that for LGBTQ users, Tumblr simultaneously generates the specter of a "queer utopia"—a space where queer potential flourishes and more expansive ways to think about the future materialize—and queer "vortextuality"—an experience of being sucked into an online black hole with severe limitations. Furthermore, the user experience on the site underscores the profound vulnerability of queer individuals and communities in digital, corporatized space.